Horrid henry's purple hand gang joke book - Simon, Francesca (Orion Children's Books UK, 2011)
Laugh your head off with Horrid Henry, Rude Ralph and the rest of the Purple Hand Gang as they present a selection of the best, most hilarious, ridiculously ribtickling jokes sent in by Horrid Henry fans everywhere.